Aerobic Oxidative Heck/Dehydrogenation Reactions of Cyclohexenones: Efficient Access to meta‐Substituted Phenols1. Issue 13 (19th February 2013) - Izawa, Yusuke; Zheng, Changwu; Stahl, Shannon S.
<x xml:space="preserve">Abstract</x> Jockeying for the (meta)position: A new dicationic palladium(II) catalyst, employing a 6, 6′‐dimethyl‐2, 2′‐bipyridine ligand, promotes both the aerobic oxidative Heck coupling and dehydrogenation reactions of cyclohexenones. These reactions may be combined in a one‐pot sequence to enable the straightforward synthesis of meta‐substituted phenols (see scheme).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>